The respiratory effects of occupational polypropylene flock exposure - Atis, S; Tutluoglu, B; Levent, E; Ozturk, C; Tunaci, A; Sahin, K; Saral, A; Oktay, I; Kanik, A; Nemery, B (EUROPEAN RESPIRATORY SOC JOURNALS LTD, 2005)
The present study evaluated the possible effects of exposure to polypropylene flock on respiratory health and serum cytokines in a cross-sectional study of workers from a plant in Turkey. A total of 50 polypropylene flocking workers were compared to a control group of 45 subjects. All subjects filled out a respiratory questionnaire and underwent a physical examination, a chest radiograph and pulmonary function testing, including single breath carbon monoxide diffusing capacity (DL,CO). Serum interleukin-8 (IL-8) and tumour necrosis factor-alpha (TNF-alpha) were measured. Additionally, high resolution computed tomography (HRCT) of the chest was performed in 10 exposed workers with low DL,CO. Work-related respiratory symptoms were reported in 26% of the exposed subjects and in 13.3% of the controls. Logistic regression analysis showed that the risk of respiratory symptoms increased 3.6 fold in polypropylene flocking workers when compared to controls. Parameters of the study group, including per cent predicted: forced vital capacity, forced expiratory volume in one second, forced mid-expiratory flow 25-75% and DL,CO, were significantly lower than in controls. Multivariate analyses showed that being a polypropylene flocking worker was a predictive factor for impairment of pulmonary function. Serum IL-8 and TNF-alpha levels were increased in the study group compared with the controls. HRCT revealed peribronchial thickening and diffuse ground glass attenuation in some subjects. The present study suggests the presence of subtle or the beginning of interstitial lung disease in these polypropylene flocking workers.
Keywords: cytokine; interstitial lung disease; lung function; occupational lung disease; polypropylene flock; respirable dust; INTERSTITIAL LUNG-DISEASE; IDIOPATHIC PULMONARY-FIBROSIS; NEUTROPHIL CHEMOTACTIC FACTOR; WORKERS LUNG; INTERLEUKIN-8; COMMUNITY; PLANT; DUST; RATS; Respiratory System